2022
DOI: 10.1007/s12079-022-00672-4
|View full text |Cite
|
Sign up to set email alerts
|

The network map of urotensin-II mediated signaling pathway in physiological and pathological conditions

Abstract: Urotensin‐II is a polypeptide ligand with neurohormone‐like activity. It mediates downstream signaling pathways through G‐protein‐coupled receptor 14 (GPR14) also known as urotensin receptor (UTR). Urotensin‐II is the most potent endogenous vasoconstrictor in mammals, promoting cardiovascular remodelling, cardiac fibrosis, and cardiomyocyte hypertrophy. It is also involved in other physiological and pathological activities, including neurosecretory effects, insulin resistance, atherosclerosis, kidney disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Lipopolysaccharide stimulated the UII system to activate migration and increase cytokine gene levels in frog leukocytes ( Tomiyama et al, 2015 ). Other studies have reported the proinflammatory action of the UII system in cells and circulation ( Clavier et al, 2020 ; Liu et al, 2015 ; Rex et al, 2022 ; Sun and Liu, 2019 ). UII also stimulates fibrosis in various tissues, including the heart, liver, and kidney ( Kemp et al, 2009 ; Liang et al, 2021 ; Liu et al, 2009 ; Tian et al, 2008a ; Zhang et al, 2007 ).…”
Section: Urotensin II System In Glomerulonephritismentioning
confidence: 95%
“…Lipopolysaccharide stimulated the UII system to activate migration and increase cytokine gene levels in frog leukocytes ( Tomiyama et al, 2015 ). Other studies have reported the proinflammatory action of the UII system in cells and circulation ( Clavier et al, 2020 ; Liu et al, 2015 ; Rex et al, 2022 ; Sun and Liu, 2019 ). UII also stimulates fibrosis in various tissues, including the heart, liver, and kidney ( Kemp et al, 2009 ; Liang et al, 2021 ; Liu et al, 2009 ; Tian et al, 2008a ; Zhang et al, 2007 ).…”
Section: Urotensin II System In Glomerulonephritismentioning
confidence: 95%
“…Atherosclerosis is the most important pathological bases of cardiovascular and cerebrovascular diseases, including myocardial infarctions, strokes, and disabling peripheral artery disease [ 3 ]. Urotensin II (UII), a cyclic peptide of 11 amino acids that was first discovered in teleost fish, is also linked to the pathophysiology and physiology of the heart [ 4 , 5 ]. Previous studies identified a G-protein-coupled orphan receptor 14 (GPR14) as the UII receptor (UTR) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%